Sustainability and Economic Growth : The Role of Green Investment in Developing Economies - Rizki Tri Atmojo; Bagus Nurlistyawan (International Forum of Researchers and Lecturers, 2024)
The shift towards sustainable development has become a central concern in global economic strategies. This paper assesses the role of green investment in fostering economic growth while ensuring environmental sustainability in developing economies. By analyzing investments in renewable energy, sustainable agriculture, and eco-friendly technologies, the study evaluates the potential for green investments to stimulate job creation, enhance economic resilience, and reduce environmental degradation. The paper also explores policy frameworks that could incentivize green investments and support the transition to a low-carbon economy.